Geographic constraints and the housing supply elasticity in Germany - Eyayaw Beze (RWI - Leibniz-Institut für Wirtschaftsforschung, 2023)
The study estimates the housing supply elasticity and the impact of geographic constraints in Germany from 2008-2019 using the Bartik instrument. The results show that the housing supply is, on average, inelastic, with a floorspace elasticity of 0.22 and a units elasticity of 0.25. The study also reveals that geographical constraints partially affect the housing supply elasticity across districts. Notably, high development intensity decreases the elasticity, while the unavailability of land for development due to restrictive geography has no significant impact on the housing supply elasticity. The housing supply elasticity estimates may prove useful for calibrating quantitative urban or regional models in Germany. – – In der Studie werden die Elastizität des Wohnungsangebots und die Auswirkungen geografischer Beschränkungen in Deutschland im Zeitraum 2008-2019 mithilfe des Bartik-Instruments geschätzt. Die Ergebnisse zeigen, dass das Wohnungsangebot im Durchschnitt unelastisch ist, mit einer Flächenelastizität von 0,22 und einer Einheitenelastizität von 0,25. Die Studie zeigt auch, dass geografische Zwänge die Elastizität des Wohnungsangebots in den einzelnen Bezirken teilweise beeinflussen. Vor allem eine hohe Bebauungsintensität verringert die Elastizität, während die Nichtverfügbarkeit von Bauland aufgrund restriktiver geografischer Gegebenheiten keine signifikanten Auswirkungen auf die Elastizität des Wohnungsangebots hat. Die Schätzungen der Wohnungsangebotselastizität können sich als nützlich für die Kalibrierung quantitativer Stadt- oder Regionalmodelle in Deutschland erweisen.
Keywords: R31; 330; House prices; housing supply; housing supply elasticity